Central South America - Marengo, José A. (2020)
Heavy rainfall events were observed in January along the dry southern coast of Peru, resulting in some locations breaking precipitation records of more than 30 years. Heavy rainfall during February led to 42 landslides across Peru and, by the end of summer, 77 people were reported dead, 165 wounded, and 3285 affected. More than 2600 homes were destroyed by floods and landslides. In the Bolivian Andes, an intense rainfall event triggered flash floods when 55 mm fell in Cochabamba on 20 February. This was Cochabamba’s fourth-highest daily precipitation on record and produced 2019’s biggest flood on the Rocha River.